Peran Mediasi Customer Value dalam Pengaruh Experiential Marketing dan Product Quality terhadap Brand Loyalty - Mohamad Rafi Ahdan Rizar; Nasharuddin Mas; Alfiana Alfiana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This quantitative study investigates the antecedents of Brand Loyalty in Genshin Impact players by examining the mediating role of Customer Value in the relationship between Experiential Marketing and Product Quality. Data were collected from 80 active players in Malang City using a purposive sampling technique and analyzed using a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach to examine the relationship between variables. The results revealed two distinct pathways to loyalty formation. First, Experiential Marketing demonstrated a significant influence on Brand Loyalty, both directly and indirectly through strong mediation by Customer Value. This suggests that emotional, sensory, and relational experiences during gameplay play a crucial role in creating perceived value and long-term engagement. Second, although Product Quality demonstrated a significant direct influence on Brand Loyalty, its influence was not significantly mediated by Customer Value. This indicates that while the game's graphical quality, system performance, and technical stability are highly appreciated, they do not automatically translate into customer value without a meaningful experience. This study concludes that in the Games-as-a-Service model, loyalty is built through a dual strategy: a combination of superior product appeal and holistic value creation derived from a rich, curated player experience. Therefore, game developers need to synergistically integrate experience and quality strategies to build long-term brand loyalty. The practical implications of these findings are highly relevant for game developers and digital marketers. Marketing strategies are no longer sufficient to simply highlight technical features or product specifications; they must also address the emotional and social dimensions experienced by players.